1996
DOI: 10.1128/jb.178.11.3384-3388.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and analysis of aklaviketone reductase from Streptomyces sp. strain C5

Abstract: DNA sequence analysis of a region of the Streptomyces sp. strain C5 daunomycin biosynthesis gene cluster, located just upstream of the daunomycin polyketide biosynthesis genes, revealed the presence of six complete genes. The two genes reading right to left include genes encoding the potentially translationally coupled gene products, an acyl carrier protein and a ketoreductase, and the four genes reading divergently, left to right, include two open reading frames of unknown function followed by a gene encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…Other entries in the protein identification databases were also found in routine searches using the Orf2'" sequence, including DnrS and DauH from daunorubicin (daunomycin)-producing S. peucetius (Otten et al, 1995) and Streptomyces sp. strain C5 (Dickens et al, 1996), respectively, but the closest match (50 % identity) was found with the product of eryCZIl (orf8) from the erythromycin producer, Saccharopolyspora erythraea (Haydock, 1992). These proteins all contain a consensus sequence motif (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other entries in the protein identification databases were also found in routine searches using the Orf2'" sequence, including DnrS and DauH from daunorubicin (daunomycin)-producing S. peucetius (Otten et al, 1995) and Streptomyces sp. strain C5 (Dickens et al, 1996), respectively, but the closest match (50 % identity) was found with the product of eryCZIl (orf8) from the erythromycin producer, Saccharopolyspora erythraea (Haydock, 1992). These proteins all contain a consensus sequence motif (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The acyltransferase encoded by dpsD has been speculated to function as propionyl-SCoA:acyl carrier protein (ACP)-SH acyltransferase (41). The gene encoding ACP, dpsG, is located about 6.8 kbp upstream of the genes encoding the daunorubicin KS ␣ and KS ␤ (8,12,41). Because the daunorubicin/doxorubicin PKS gene cluster of Streptomyces sp.…”
mentioning
confidence: 99%
“…The aglycone is formed by condensing nine extender units derived from malonyl coenzyme A onto a propionyl moiety to make a C 21 polyketide intermediate (21,23,(42)(43)(44)(45)50), which is reduced at C-9 from the carboxy terminus (43,44), cyclized, and aromatized to form aklanonic acid (18,19,23,40,(42)(43)(44). Aklanonic acid is converted in four steps to ε-rhodomycinone (3,7,15,16,30,40,42,44), an intermediate that is accumulated in large quantities by most daunorubicin-producing strains (27,42,44,46). It is postulated that ε-rhodomycinone is glycosylated by condensation with TDP-daunosamine (3,8,23,38,42,44) to form the first glycoside intermediate, here named rhodomycin D, which is then converted by a series of reactions to daunorubicin and doxorubicin.…”
mentioning
confidence: 99%